Transformation of gated community in the last three decades in Medan City, Indonesia - Dwira Nirfalini Aulia; Beny OY Marpaung (Institut Teknologi Sepuluh Nopember, 2017)
The growth and development of Gated Community are happening around the world with no exception in Indonesia. The development happened because of rapid urban growth caused by urbanization. The important results from studying the transformation of gated community are the trend and factors that cause the change. The purpose of this research is to predict, prepare and control the growth of formal urban housing in the future. Factors led to the emergence and growing rapidly of a gated community in Southeast Asia is a combination of socio-economic background, culture, and security. Research is conducted by two approaches. Firstly, are the external aspects such as regulation of formal housing, political condition, and real estate market condition. Secondly, are the internal issues such as the concept of settlement planning and the characteristics of the occupants. This study was conducted in three residential development in the city of Medan which represent in the 1980's, 1990's and 2000's, namely Taman Setia Budi Indah, Graha Bumi Asri and Graha Metropolitan. The research’s result shows the factors of changes occur in the privatization of public space, exclusivity and the need for security. The indirect phenomenon of gated community growth is a reflection of a modern city life's critique, because of the safety reduced. If these are not anticipated soon, it will form the structure of fragmented urban space with the privatization of public space legally